Attrition in ODL : a macro perspective in reducing non-completion rate among LLL learners - Santhi, Raghvan; Mohd Ghazali Mohayidin; Loo, Sin Chun; Ariff Syah Juhari (2014)
Increasing student attrition at high rates in Open and Distance Learning (ODL) institutions is a phenomenon which has not been fully understood. Generally, much literature has been produced to explore student attrition in the conventional higher education settings, which provides guidance as to possible factors that may influence attrition. Many factors affecting student attrition have been identified; however, these results have only benefited the traditional institution of higher education that promotes full-time learning, but have not helped the attrition rates at ODL institutions that supports formal learning via lifelong learning (LLL). Today, in the advent of the Internet and its digital technologies, focus on LLL, online education and adult learning is more evident. ODL institutions in Malaysia have now reached the mainstream of education via lifelong learning through formal learning. Therefore, a major benefit of this research is to provide conclusive results, which are to be used to work towards successfully reducing student attrition at ODL institutions, and, in turn, increase their completion rates. (Abstract by authors)